IMPACT OF COMPANY INCOME TAX ON CORPORATE PROFITABILITY IN NIGERIA - Adefunke, Akadakpo Bukola; Usiomon, Akogo Obehioye (Indian Journal of Finance and Banking, 2022)
The study examined the impact of company income tax on corporate performance. The study used data from twelve (12) listed firms on the Nigerian Stock Exchange, of which data for the study was collected from the annual reports of the companies, and regression analysis was used as a technique for data analysis using SPSS 2020. The data span across ten (10) years from the period of 2011-2020. Findings from the study revealed that Company income tax (CIT) has a positive and significant effect on profit after tax (PAT) and returns on equity (ROE). Change in shareholders’ funds (CSHF) has a negative yet significant effect on ROE, while CIT has a significant and positive effect on shareholders' earnings. Following the results from the research analysis, the study recommended that the fiscal policy adopted in Nigeria should consider the circumstances surrounding the activities of companies located in the Country and the special role they play in the pursuit of the economic growth of the nation. Tax incentives and positive tax reforms that could reduce the burden and liability of tax on companies in Nigeria should be incorporated in the fiscal policy to encourage their business activities and going concerns. JEL Classification Codes: H25, O16.